Social media for enhancing student engagement: The use of Facebook and blogs at a University of Technology - Ivala, E; Gachago, D (South African Journal of Higher Education, 2016)
This work investigates the promise of Facebook and blogs for enhancing students’ levels of engagement in learning. This issue warrants investigation because there is little published empirical work on the subject. The researchers applied a learning ecology perspective to study the potential of Facebook and blogs in enhancing student levels of engagement in learning. In-depth interviews with lecturers who use Facebook and blogs and focus groups with their respective students were carried out to establish: usage in teaching and learning; the context of use; challenges encountered in usage; and whether these technologies enhanced student learning. A significant finding of the study was that appropriate use of blogs and Facebook groups, if accepted by students as a learning tool, enhances students’ engagement in learning activities of an academic nature on- and off-campus. The paper also suggests strategies for the implementation of Facebook and blogs in ways that are likely to have a positive impact on student levels of engagement.